Peningkatan Kompetensi Digital Pengurus Koperasi Melalui Pelatihan Operator Komputer Madya - Tati Suprapti; Cep Lukman Rohmat; Ahmad Muhaimin; Ai Sri Nurmala (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Intermediate Computer Operator Training is a program designed to improve the digital competence of cooperative administrators in facing the challenges of the digitalization era. The program aims to provide an in-depth understanding of the use of office software, data management, and digital applications relevant to cooperative operations. The training method includes interactive theoretical and practical sessions to improve participants' skills in operating computers and managing information effectively. The results of the training showed a significant increase in participants' understanding of digital technology. In addition, the training also had a positive impact on the efficiency of the cooperative board's work in administrative and financial management. Evaluations conducted through tests and questionnaires showed that most participants felt more confident in using computers and supporting software after attending the training. In the era of digital transformation, increasing digital literacy for cooperative boards is an urgent need to improve the competitiveness and sustainability of cooperative businesses. With this training, it is expected that cooperatives can be more adaptive to technological developments and be able to take advantage of digitalization to increase productivity and transparency in business management.